2
$\begingroup$

By considering $f(z)=exp(z-\frac{1}{z})$ show that

$$ \frac{1}{2\pi}\int_{0}^{2\pi}cos(n\theta-2sin\theta)d\theta=\sum_0^{\infty}\frac{(-1)^k}{k!(n+k)!}\ \forall n\ge1$$


f is holomorphic in $\gamma (0,R)$\{$0$} $\forall R$ so I tried the Laurent series formula about $0$:

$$c_n=\frac{1}{2i\pi}\int \frac{f(w)}{w^{n+1}}dw$$

now setting $w = exp(i\theta)$ and $f(z)=exp(z - \frac{1}{z})$ as per the hint

$$c_n=\frac{1}{2i\pi}\int_{\gamma(0,1)} \frac{e^{e^{i\theta}-e^{-i\theta}}}{e^{n{i\theta}}}id\theta=\frac{1}{2\pi} \int e^{i(2sin\theta-n\theta)} d\theta$$

and then I guess

$$\sum_{-\infty}^{\infty} c_n z^n = f(z) = exp (z - 1/z) = \sum_{0}^{\infty} \frac {(z-1/z)^n}{n!}=\sum_{0}^{\infty}\frac{\sum_{k=0}^n{C_n^k z^k (-1/z)^{n-k}}}{n!}$$

i then tried to collect $c_n$ and $c_{-n}$ but really I am no longer sure :(

$\endgroup$
4
  • $\begingroup$ Hint $\Re[exp(i((n\phi)-2\sin(n \phi))]=\cos((n\phi)-2\sin(n \phi))$ the rest seems to be correct $\endgroup$ – tired Jun 22 '15 at 14:25
  • $\begingroup$ yes but I thought I would leave as is to allow the collection of c_{n} and c_{-n} , since the Laurent series goes to +/_ infinity , unlike the power series ? $\endgroup$ – user3203476 Jun 22 '15 at 14:29
  • 1
    $\begingroup$ You have to compute a single coefficient of the whole Laurent series, i.e. the coefficient of $z^n$. Things went bad just because you used $n$ as summation variable in too many places. Try expanding $f(z)$ as $$\sum_{m\geq 0}\frac{\left(z-\frac{1}{z}\right)^m}{m!}$$ and now ask yourself what is the coefficient of $z^n$ in the last sum. $\endgroup$ – Jack D'Aurizio Jun 22 '15 at 14:38
  • $\begingroup$ But for a given n there will be contributions from multiple m's ? $\endgroup$ – user3203476 Jun 22 '15 at 15:32
0
$\begingroup$

Following the suggestion of user Jack d'Aurizio (thank you), I am trying to identify the coefficient of a particular $z^n$ in:

$$ \sum_{m-0}^{\infty} \frac {(z-1/z)^m}{m!}=\sum_{m=0}^{\infty}\frac{\sum_{k=0}^m{C_m^k z^k (-1/z)^{m-k}}}{m!} = \sum_{m=0}^{\infty}\frac{\sum_{k=0}^m{C_m^k z^{2k-m} (-1)^{m-k}}}{m!}$$

now for a particular $z^n$ there will be one contribution each from each $m$ : the contribution from the k in the inner sum such that $2k-m=n$

So the coefficient of a $z^n$ is, summing over all the $m$:

$$ \sum_{m=0}^{\infty}\frac{C_{m}^{(m+n) \over 2} (-1)^{ {m-n} \over 2}}{m!} $$

for the cases where $ {m+n} \over 2$ is even but that is still not the neat answer that i was asked to reach ...

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.